Comparison of Synovex-S® and two levels of Revalor-S® in heavy-weight Holstein steers - Kuhl, Gerry L.; Simms, D.D.; Blasi, Dale A.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In two field trials, 434 Holstein steers averaging 849 lbs were assigned randomly to three single implant treatments: 1) Synovex- S®, 2) Revalor®-S 120 (120 mg trenbolone acetate (TBA) + 24 mg estradiol), and 3) Revalor®-S 140 (140 mg TBA + 28 mg estradiol). Revalor-implanted steers gained .05 to .10 lb per day faster, but this improvement was not statistically significant (P>.05). Both Revalor-implanted groups produced trimmer carcasses with less (P<.05) backfat than Synovex steers. All other carcass characteristics and beef sensory properties, including taste panel evaluations of tenderness, juiciness, and flavor, were not influenced by implant used.
Keywords: Beef; Synovex; Revalor; Holsteins; Feedlot; Carcass traits